Limited Effects of Inorganic Nitrate Supplementation on Exercise Training Responses: A Systematic Review and Meta-analysis - Austin C. Hogwood; Kara C. Anderson; Joaquin Ortiz de Zevallos; Craig Paterson; Arthur Weltman; Jason D. Allen (SpringerOpen, 2023)
Abstract Background Inorganic nitrate (NO3 −) supplementation is purported to benefit short-term exercise performance, but it is unclear whether NO3 − improves longer-term exercise training responses (such as improvements in VO2peak or time to exhaustion (TTE)) versus exercise training alone. The purpose of this systematic review and meta-analysis was to determine the effects of NO3 − supplementation combined with exercise training on VO2peak and TTE, and to identify potential factors that may impact outcomes. Methods Electronic databases (PubMed, Medscape, and Web of Science) were searched for articles published through June 2022 with article inclusion determined a priori as: (1) randomized placebo-controlled trials, (2) exercise training lasted at least three weeks, (3) treatment groups received identical exercise training, (4) treatment groups had matched VO2peak at baseline. Study quality was assessed using the Cochrane Risk-of-Bias 2 tool. Standardized mean difference (SMD) with 95% confidence intervals (CI) were calculated using restricted maximum likelihood estimation between pre- and post-training differences in outcomes. Moderator subgroup and meta-regression analyses were completed to determine whether the overall effect was influenced by age, sex, NO3 − dosage, baseline VO2peak, health status, NO3 − administration route, and training conditions. Results Nine studies consisting of eleven trials were included: n = 228 (72 females); age = 37.7 ± 21 years; VO2peak: 40 ± 18 ml/kg/min. NO3 − supplementation did not enhance exercise training with respect to VO2peak (SMD: 0.18; 95% CI: -0.09, 0.44; p = 0.19) or TTE (SMD: 0.08; 95% CI: − 0.21, 0.37; p = 0.58). No significant moderators were revealed on either outcome. Subset analysis on healthy participants who consumed beetroot juice (BRJ) revealed stronger trends for NO3 − improving VO2peak (p = 0.08) compared with TTE (p = 0.19), with no significant moderators. Sunset funnel plot revealed low statistical power in all trials. Conclusions NO3 − supplementation combined with exercise training may not enhance exercise outcomes such as VO2peak or TTE. A trend for greater improvement in VO2peak in healthy participants supplemented with BRJ may exist (p = 0.08). Overall, future studies in this area need increased sample sizes, more unified methodologies, longer training interventions, and examination of sex as a biological variable to strengthen conclusions.